Brucellosis: An underdiagnosed infection in children - Patil, Sooraj; Verma, Sanjay; Mishra, Purbasha; Sharma, Megha; Gautam, Vikas; Ray, Pallab; Sethi, Sunil (Indian Journal of Child Health, 2019)
Brucellosis, which is believed and categorized as an animal disease, can, surprisingly, be found in humans also. We report a 5-year boy presenting to us with prolonged (5 months) unexplained fever, non-tender discrete lymphadenopathy, and hepatosplenomegaly and finally proved to be a case of brucellosis, which was treated appropriately. Brucellosis should be considered as one of the differential diagnoses causing prolonged fever in children.